Self‐care tools to treat depressive symptoms in patients with age‐related eye disease: a randomized controlled clinical trial. (16th January 2017) - Kamga, Hortence; McCusker, Jane; Yaffe, Mark; Sewitch, Maida; Sussman, Tamara; Strumpf, Erin; Olivier, Sébastien; Wittich, Walter; Moghadaszadeh, Solmaz; Freeman, Ellen E
Abstract: Background: Depression is very common in people with age‐related eye disease. Our goal was to determine if self‐care tools plus limited telephone support could reduce depressive symptoms in patients with age‐related macular degeneration or diabetic retinopathy. Design: A single‐blind randomized controlled clinical trial was conducted at Maisonneuve‐Rosemont Hospital in Montreal, Canada. Participants: Eighty participants were recruited. Methods: To be eligible, participants must have had either late stage age‐related macular degeneration or diabetic retinopathy, at least mild depressive symptoms, and visual acuity better than 20/200. Half were randomized to the intervention arm and half to delayed intervention/usual care. The intervention consisted of large print written and audio tools incorporating cognitive‐behavioral principles plus three 10‐minute telephone calls from a lay coach. Eight‐week follow‐up data were collected by telephone. Main Outcome Measures: The primary outcome was the 8‐week change in depressive symptoms as measured by the Patient Health Questionnaire‐9. Secondary outcomes included anxiety, life space and self‐efficacy. Results: The baseline mean logMAR visual acuity was 0.37 (SD = 0.20), and the baseline mean Patient Health Questionnaire‐9 score was 9.5 (SD = 3.9) indicating moderate depressive symptoms. After adjusting for baseline imbalances in visual acuity, the intervention reduced depressive symptoms by 2.1 points more than usual care ( P = 0.040). The intervention was not associated with the secondary outcomes ( P > 0.05). Conclusions: Self‐care tools plus telephone coaching led to a modest improvement in depressive symptoms in patients with age‐related eye disease. Additional research on how to maximize their effect is necessary.